Resilience of Rainfed Lowland Farming Communities on the Threat of Food Insecurity due to Climate Change (A Case in South Lampung) - Siti Mariyani; Nurmala K Pandjaitan; Martua Sihaloho (Sodality: Jurnal Sosiologi Pedesaan, 2019)
Rain-fed lowland has a risk of drought, flooding, nutrient imbalance, and increasing pest and weed disturbance. These conditions will get worse when experiencing climate change. This can cause a decrease in production, so the community needs to develop strategies to survive in facing the threat of food insecurity. The purpose of this study was to analyze the resilience of rain-fed farming communities against the threat of food insecurity due to climate change. The study was conducted in the Marga Kaya Village, Lampung Province. Data was collected using a survey method by taking 100 respondents with simple random sampling. The results showed that the rain-fed farming community has been resilient to face the threat of food insecurity due to climate change. Rain-fed farming community through a network of adaptive capacity, especially social capital and manage available resources can maintain the existence of institutional barns to face the threat of food insecurity.